DOCK2 as a novel CD11c ligand in neutrophils to regulate reactive oxygen species production - Koutsogiannaki, Sophia; Hou, Lifei; Alhamdan, Fahd; Mastali, Mitra; Murray, Christopher; Van Eyk, Jennifer; Kunimura, Kazufumi; Yuki, Koichi (Frontiers in Immunology, 2025)
CD11c (integrin αX) is one of the β2 integrin members traditionally recognized as a dendritic cell marker. It forms the CD11c/CD18 heterodimer—also known as complement receptor 4 (CR4)—and mediates ligand binding to complement fragments, fibrinogen, and intercellular adhesion molecules in vitro. Although its expression on dendritic cells and a subset of macrophage populations has been well recognized historically, recent findings reveal that it demonstrates a broader expression profile, including in neutrophils. In neutrophils, CD11c is predominantly intracellular, suggesting a non-canonical role beyond cellular adhesion. We previously identified IQGAP1 as an intracellular binding partner of CD11c/CD18, implicating this interaction in neutrophil maturation. Here, mature CD11c-deficient neutrophils displayed impaired reactive oxygen species (ROS) generation while maintaining normal phagocytosis, indicating a selective defect in oxidative burst. Given the central role of NADPH oxidase and Rac activation in ROS production, we hypothesized that CD11c would influence this pathway. Phosphoproteomic profiling revealed reduced phosphorylation of the Rac guanine nucleotide exchange factor DOCK2 in CD11c-deficient neutrophils upon phorbol 12-myristate 13-acetate (PMA) stimulation. The analysis involving immunoprecipitation and proteomics confirmed a CD11c–DOCK2 association. These results supported a model in which CD11c would directly engage DOCK2 to promote Rac activation and NADPH oxidase function, uncovering a novel integrin-mediated mechanism regulating neutrophil effector activity. This work expands the functional repertoire of CD11c and provides a new insight into integrin signaling in innate immunity.